2015
DOI: 10.1002/jcp.24814
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Attenuates Cytokine‐Induced Remodeling in Human Fetal Airway Smooth Muscle Cells

Abstract: Asthma in the pediatric population remains a significant contributor to morbidity and increasing healthcare costs. Vitamin D3 insufficiency and deficiency have been associated with development of asthma. Recent studies in models of adult airway diseases suggest that the bioactive Vitamin D3 metabolite, calcitriol (1,25-dihydroxyvitamin D3; 1,25(OH)2D3), modulates responses to inflammation; however this concept has not been explored in developing airways in the context of pediatric asthma. We used human fetal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 40 publications
7
37
0
1
Order By: Relevance
“…Treatment with calcitriol also attenuated TNF-α and TGF-β-induced collagen III expression and deposition and inhibited proliferation of fetal ASM cells mediated by the ERK signaling pathway. 31 Characterization of differences in transcriptome responsiveness to vitamin D between fatal asthma and control ASM cells by RNA sequencing have highlighted 838 differentially expressed genes in fatal asthma. Treatment with vitamin D was shown to induce differential expression of 711 genes in fatal asthma and 867 genes in control ASM cells.…”
Section: Results From Human Studiesmentioning
confidence: 99%
“…Treatment with calcitriol also attenuated TNF-α and TGF-β-induced collagen III expression and deposition and inhibited proliferation of fetal ASM cells mediated by the ERK signaling pathway. 31 Characterization of differences in transcriptome responsiveness to vitamin D between fatal asthma and control ASM cells by RNA sequencing have highlighted 838 differentially expressed genes in fatal asthma. Treatment with vitamin D was shown to induce differential expression of 711 genes in fatal asthma and 867 genes in control ASM cells.…”
Section: Results From Human Studiesmentioning
confidence: 99%
“…Briefly, ASM cells were enzymatically dissociated from tracheobronchial tissue of de-identified non-viable 18–22 week gestation fetuses (Dr. Pandya or from Novogenix Los Angeles, CA; protocols approved and considered exempt by the Mayo Institutional Review Board and Ethics Committees in the UK). Persistence of smooth muscle phenotype was verified by expression of smooth muscle myosin and actin and Ca 2+ regulatory proteins, but lack of expression of E-cadherin (epithelial marker) [53, 54]. …”
Section: Methodsmentioning
confidence: 99%
“…The 1,25(OH) 2 D 3 was also able to downregulate the protein and mRNA expression of matrix metalloproteinase-9 (MMP-9) and a disintegrin metalloprotease-33 (ADAM-33), both of which play a role in airway remodeling and increased disease severity associated with allergic asthma [63]. The vitamin D 3 metabolite was also able to inhibit proliferation of fetal ASM cells induced by TNF-α and TGF-β via the ERK-mediated signaling pathway [64]. Treatment of human ASM cells with calcitriol inhibited platelet-derived growth factor (PDGF)-induced ASM growth by inhibiting phosphorylation of retinoblastoma protein (Rb) and checkpoint kinase 1 (Chk1).…”
Section: Vitamin D and Airway Smooth Muscle Cell Functionmentioning
confidence: 99%
“…Using human fetal ASM cells as a model of the early post natal airways, it was found that calcitriol attenuated TNF-α enhancement of MMP-9 expression and activity as well as TNF-α and TGF-β induced collagen II expression and deposition [64]. These mediators are known to contribute to epithelial-mesenchymal transition (EMT) and airway remodeling [66].…”
Section: Vitamin D and Airway Smooth Muscle Cell Functionmentioning
confidence: 99%